A kind of amphiphilic organic zinc salt and its preparation method and application
By using amphiphilic organic zinc salt in aqueous zinc ion batteries, the corrosion and dendrite problems of zinc negative electrodes are solved, and the cycle stability and Coulomb efficiency of the battery are significantly improved.
Patent Information
- Application Number
- CN202310155247.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-21
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2043-02-21
AI Technical Summary
The existing aqueous zinc ion batteries have shortcomings in terms of cycle stability and Coulomb efficiency, mainly due to the corrosion of zinc negative electrode and dendrites.
The amphiphilic organic zinc salt is used as the electrolyte component and is prepared by chemical reaction between acid imide and zinc source to optimize the interface structure of the metal zinc-electrolyte to inhibit corrosion and dendrites.
It significantly improves the cycle stability of aqueous zinc ion batteries, extends the cycle life of the battery, and improves battery performance.
Smart Images

Figure CN116143669B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to aqueous zinc ion battery electrolyte, and more specifically, relates to an amphiphilic organic zinc salt and a preparation method and application thereof. Background Art
[0002] Secondary battery energy storage is one of the important technologies to support the transformation of energy structure. Energy storage technology represented by lithium-ion batteries has been commercialized to a certain extent. However, lithium-ion batteries currently use an electrolyte formula of flammable organic solvents and lithium salts. In addition, the highly active lithium-containing compounds produced during the charging and discharging process often lead to thermal runaway and combustion or even explosion when the battery is damaged by external forces or internal short circuits. In addition to safety hazards, the scarcity of lithium ore resources also restricts the use of lithium-ion batteries to a certain extent. For this reason, it is urgent to develop new secondary battery technologies with high safety and low cost.
[0003] Compared with highly active lithium-ion batteries, aqueous zinc-ion batteries with moderately active metal zinc as the negative electrode have received widespread attention in recent years. Their advantages mainly include the following four points: First, this type of battery uses an aqueous solution of zinc salt as the electrolyte. The inherent non-flammable property of this type of electrolyte greatly improves the safety of the battery. Second, Zn 2+ The electrode potential of the Zn / Zn pair is only -0.763V (relative to the standard hydrogen electrode). Using zinc metal as the negative electrode can broaden the operating voltage range of the battery. Third, zinc metal has a high mass specific capacity (820mAh g -1 ) and volumetric capacity (5854 mAh cm -3 ). Fourth, zinc ore resources are abundant, and the cost of zinc-based batteries is generally low. Therefore, the development of low-cost, high-safety aqueous zinc-ion batteries has a high practical significance.
[0004] The electrolytes commonly used in aqueous zinc-ion batteries are aqueous solutions of various water-soluble zinc salts, such as aqueous zinc sulfate solution, aqueous zinc chloride solution, aqueous zinc trifluoromethanesulfonate solution, aqueous zinc trifluoromethanesulfonimide solution, etc. Due to the hydrolysis of zinc ions, the above electrolytes are generally weakly acidic, which will aggravate the chemical corrosion and electrochemical hydrogen evolution of metallic zinc in weakly acidic electrolytes. In addition, the zinc dendrite problem of metallic zinc in traditional aqueous electrolytes is also very serious. Limited by the above two aspects, the cycle stability and coulomb efficiency of aqueous zinc-ion batteries with metallic zinc as the negative electrode are difficult to meet the actual needs of production and life. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the present invention provides an amphiphilic organic zinc salt and a preparation method and application thereof. The zinc salt can be directly prepared by the chemical reaction of an acidic imide and a zinc source. The electrolyte prepared with the zinc salt can optimize the interface structure of metal zinc-electrolyte, inhibit the corrosion and dendrite problems of the zinc negative electrode in the aqueous electrolyte, thereby significantly improving the cycle stability of the aqueous zinc ion battery.
[0006] To achieve the above object, according to one aspect of the present invention, the present invention provides a method for preparing an amphiphilic organic zinc salt, the method comprising the following steps:
[0007] (1) dissolving an imide in water, adding a zinc source to the obtained solution and then heating it;
[0008] (2) Cooling the mixed solution obtained in step (1) to room temperature and filtering it, and heating the obtained filtrate to obtain an amphiphilic organic zinc salt.
[0009] Furthermore, the imide is selected from one of N-(benzenesulfonyl)benzenesulfonamide, N-(methylsulfonyl)benzenesulfonamide, N-(trifluoromethylsulfonyl)benzenesulfonamide and N-(trifluoromethylsulfonyl)methanesulfonamide.
[0010] Furthermore, in step (1), the heating temperature is 50-100° C. and the reaction time is 0.5-10 h.
[0011] Furthermore, the heating temperature in step (2) is 80°C to 120°C.
[0012] Furthermore, the imide is N-(phenylsulfonyl)benzenesulfonamide, and the amount is 0.2 mol; the zinc source is zinc oxide, and the amount is 0.12 mol; the imide, deionized water and the zinc source are reacted with magnetic stirring at 80°C for 4 hours to obtain a mixed solution, and the filtrate obtained after the mixed solution is filtered is heated at 100°C until all water is removed to obtain an amphiphilic organic zinc salt.
[0013] The invention provides an amphiphilic organic zinc salt, which is prepared by adopting the preparation method of the amphiphilic organic zinc salt as mentioned above.
[0014] The present invention also provides a use of the amphiphilic organic zinc salt as described above in an aqueous zinc ion battery electrolyte.
[0015] Furthermore, the concentration of the amphiphilic organic zinc salt in the electrolyte is 0.1-2 mol / L.
[0016] Furthermore, the concentration of the amphiphilic organic zinc salt in the electrolyte is 1 mol / L or 0.5 mol / L.
[0017] In general, compared with the prior art, the above technical solutions conceived by the present invention mainly have the following beneficial effects:
[0018] 1. Dissolve the imide substance in water, use the acidity of the imide aqueous solution to react with different zinc sources, and then dry to obtain an amphiphilic organic zinc salt. Since the salt has a special hydrophilic / hydrophobic group structure, using the aqueous solution prepared with it as the electrolyte of the aqueous zinc ion battery can inhibit the formation of zinc dendrites during the battery cycle and the corrosion reaction between the metal zinc negative electrode and the electrolyte, thereby improving the cycle stability of the zinc negative electrode.
[0019] 2. The electrolyte prepared by the present invention has the characteristics of low cost, high safety, and convenience for large-scale production. The presence of amphiphilic zinc salt can effectively improve the chemical stability of metallic zinc in weakly acidic electrolyte and reduce the corrosion of metallic zinc by the electrolyte.
[0020] 3. The zinc salt also optimizes the interfacial structure of metallic zinc in aqueous electrolyte, thereby significantly inhibiting the growth of zinc dendrites and electrochemical hydrogen evolution during repeated charge and discharge of the battery.
[0021] 4. The amphiphilic zinc salt obtained by the preparation method provided by the present invention is a white solid powder, and the prepared electrolyte is colorless and transparent. -2 , surface capacity is 1 mAh cm -2 Under the conditions of , using the aqueous solution with a salt concentration of 1 mol / L as the electrolyte, the zinc-zinc symmetrical battery can achieve 3600 hours of repeated cycling without short circuit, and its cycle life far exceeds the cycle life of the zinc-zinc symmetrical battery using 1 mol / L zinc sulfate electrolyte.
[0022] 5. The electrolyte prepared by the present invention can effectively solve the problems of dendrites and side reactions on the zinc negative electrode side of the aqueous zinc ion battery, thereby improving the battery performance of the aqueous zinc ion battery.
[0023] 6. The zinc salt preparation method provided by the present invention has mild reaction conditions, high yield, no need for cumbersome post-treatment, has prospects for large-scale mass production, and can be conveniently applied to aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic flow chart of the preparation method of the amphiphilic organic zinc salt provided by the present invention;
[0025] Figure 2 is a cycle performance diagram of a zinc-zinc symmetric battery in the electrolyte obtained in Example 1;
[0026] Figure 3 is a cycle performance diagram of a zinc-zinc symmetric battery in the electrolyte obtained in Example 2;
[0027] Figure 4 is a cycle performance diagram of a zinc-zinc symmetric battery in the electrolyte obtained in Comparative Example 1;
[0028] Figure 5 This is a cycle performance diagram of a zinc-zinc symmetric battery in the electrolyte obtained in Comparative Example 2. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0030] See also Figure 1 The present invention provides a method for preparing an amphiphilic organic zinc salt, which mainly comprises the following steps:
[0031] Step 1: dissolve the imide in water.
[0032] The imide is dissolved in water to form a transparent, uniform solution. Preferably, the imide substance is selected from one of N-(benzenesulfonyl)benzenesulfonamide, N-(methylsulfonyl)benzenesulfonamide, N-(trifluoromethylsulfonyl)benzenesulfonamide and N-(trifluoromethylsulfonyl)methanesulfonamide.
[0033] Step 2: adding a zinc source to the solution obtained in step 1 and heating the solution.
[0034] The zinc source is selected from metallic zinc, zinc oxide, and basic zinc carbonate. The amount of the zinc source is 0.5-1 times the molar number of the imide, the heating temperature is 50-100° C., and the reaction time is 0.5-10 hours.
[0035] Step 3: Cool the mixed solution obtained in step 2 to room temperature and filter it, and heat the obtained filtrate to obtain an amphiphilic organic zinc salt. Preferably, the heating temperature is 80°C to 120°C.
[0036] In order to evaluate the performance of the obtained amphiphilic zinc salt, the prepared zinc salt was prepared into solutions of different concentrations with water, which were the final electrolytes. Preferably, the concentration of the zinc salt in the electrolyte is 0.1-2 mol / L. A 2032-type button-type zinc-zinc symmetrical battery was assembled with a glass fiber separator (GF-A type) with a diameter of 19 mm, a zinc sheet with a diameter of 16 mm (thickness 100 μm), and an aqueous electrolyte (amount 100 μL). -2 、Surface capacity 1mAh cm -2The battery is repeatedly charged and discharged at a constant current under the conditions of
[0037] The present invention also provides an amphiphilic organic zinc salt, which is prepared by the preparation method of the amphiphilic organic zinc salt. The present invention also provides an application of the amphiphilic organic zinc salt in an aqueous zinc ion battery electrolyte.
[0038] The present invention is further described in detail below with reference to specific embodiments.
[0039] Example 1
[0040] An aqueous zinc ion battery electrolyte containing an amphiphilic zinc salt comprises a solute zinc salt and a solvent water, and is prepared by the following steps:
[0041] (1) Weigh 0.2 mol of N-(phenylsulfonyl)benzenesulfonamide and dissolve it in 300 mL of deionized water.
[0042] (2) Add 0.12 mol of zinc oxide to the solution obtained in step (1), and react with magnetic stirring at 80° C. for 4 h.
[0043] (3) The mixture in step (2) is cooled to room temperature and filtered, the filtrate is collected, and then heated at 100° C. until all water is removed to obtain an amphiphilic organic zinc salt.
[0044] (4) The zinc salt prepared in step (3) is prepared into a solution with a concentration of 1 mol / L using deionized water, which is the final electrolyte used.
[0045] The electrolyte obtained in step (4) was used to assemble a 2032-type button-type zinc-zinc symmetrical battery with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). -2 , surface capacity is 1 mAh cm -2 The battery is repeatedly charged and discharged at a constant current under the conditions of Figure 2 As shown. Figure 2 It can be seen that the battery cycled for 3600 hours without short circuit.
[0046] Example 2
[0047] An aqueous zinc ion battery electrolyte containing an amphiphilic zinc salt comprises a solute zinc salt and a solvent water, and is prepared by the following steps:
[0048] (1) Weigh 0.2 mol of N-(phenylsulfonyl)benzenesulfonamide and dissolve it in 300 mL of deionized water.
[0049] (2) Add 0.12 mol of zinc oxide to the solution obtained in step (1), and react with magnetic stirring at 80° C. for 4 h.
[0050] (3) The mixture in step (2) is cooled to room temperature and filtered, the filtrate is collected, and then heated at 100° C. until all water is removed to obtain an amphiphilic organic zinc salt.
[0051] (4) The zinc salt prepared in step (3) is prepared into a 0.5 mol / L solution with deionized water, which is the final electrolyte.
[0052] The electrolyte obtained in step (4) was used to assemble a 2032-type button-type zinc-zinc symmetrical battery with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). -2 , surface capacity is 1 mAh cm -2 The battery is repeatedly charged and discharged at a constant current under the conditions of Figure 3 As shown. Figure 3 It can be seen that the battery short-circuited after cycling for 100 hours.
[0053] Example 3
[0054] An aqueous zinc ion battery electrolyte containing an amphiphilic zinc salt comprises a solute zinc salt and a solvent water, and is prepared by the following steps:
[0055] (1) Weigh 0.2 mol of N-(phenylsulfonyl)benzenesulfonamide and dissolve it in 300 mL of deionized water.
[0056] (2) Add 0.12 mol of zinc oxide to the solution obtained in step (1), and react with magnetic stirring at 80° C. for 4 h.
[0057] (3) The mixture in step (2) is cooled to room temperature and filtered, the filtrate is collected, and then heated at 100° C. until all water is removed to obtain an amphiphilic organic zinc salt.
[0058] (4) The zinc salt prepared in step (3) was prepared into a 0.1 mol / L solution with deionized water, which was the final electrolyte. The electrolyte obtained in step (4) was used to assemble a 2032-type button-type zinc-zinc symmetrical battery with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). The battery was charged at a current density of 1 mA cm -2 , surface capacity is 1 mAh cm -2 The battery is repeatedly charged and discharged at a constant current under the conditions of
[0059] Example 4
[0060] An aqueous zinc ion battery electrolyte containing an amphiphilic zinc salt comprises a solute zinc salt and a solvent water, and is prepared by the following steps:
[0061] (1) Weigh 0.2 mol of N-(methylsulfonyl)benzenesulfonamide and dissolve it in 300 mL of deionized water.
[0062] (2) Add 0.12 mol of zinc oxide to the solution obtained in step (1), and react with magnetic stirring at 80° C. for 4 h.
[0063] (3) The mixture in step (2) is cooled to room temperature and filtered, the filtrate is collected, and then heated at 100° C. until all water is removed to obtain an amphiphilic organic zinc salt.
[0064] (4) The zinc salt prepared in step (3) was prepared into a solution with a concentration of 1 mol / L with deionized water, which was the final electrolyte. The electrolyte obtained in step (4) was used to assemble a 2032-type button-type zinc-zinc symmetrical battery with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). The battery was charged at a current density of 1 mA cm -2 , surface capacity is 1mAhcm -2 The battery is repeatedly charged and discharged at a constant current under the conditions of
[0065] Example 5
[0066] An aqueous zinc ion battery electrolyte containing an amphiphilic zinc salt comprises a solute zinc salt and a solvent water, and is prepared by the following steps:
[0067] (1) Weigh 0.2 mol of N-(phenylsulfonyl)benzenesulfonamide and dissolve it in 300 mL of deionized water.
[0068] (2) Add 0.12 mol zinc oxide to the solution obtained in step (1), and react with magnetic stirring at 50° C. for 4 h.
[0069] (3) The mixture in step (2) is cooled to room temperature and filtered, the filtrate is collected, and then heated at 100° C. until all water is removed to obtain an amphiphilic organic zinc salt.
[0070] (4) The zinc salt prepared in step (3) is prepared into a solution with a concentration of 1 mol / L using deionized water, which is the final electrolyte used.
[0071] The electrolyte obtained in step (4) was used to assemble a 2032-type button-type zinc-zinc symmetrical battery with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). -2 , surface capacity is 1 mAh cm -2The battery is repeatedly charged and discharged at a constant current under the conditions of
[0072] Example 6
[0073] An aqueous zinc ion battery electrolyte containing an amphiphilic zinc salt comprises a solute zinc salt and a solvent water, and is prepared by the following steps:
[0074] (1) Weigh 0.2 mol of N-(phenylsulfonyl)benzenesulfonamide and dissolve it in 300 mL of deionized water.
[0075] (2) Add 0.12 mol of zinc oxide to the solution obtained in step (1), and react with magnetic stirring at 50° C. for 8 h.
[0076] (3) The mixture in step (2) is cooled to room temperature and filtered, the filtrate is collected, and then heated at 100° C. until all water is removed to obtain an amphiphilic organic zinc salt.
[0077] (4) The zinc salt prepared in step (3) is prepared into a solution with a concentration of 1 mol / L using deionized water, which is the final electrolyte used.
[0078] The electrolyte obtained in step (4) was used to assemble a 2032-type button-type zinc-zinc symmetrical battery with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). -2 , surface capacity is 1 mAh cm -2 The battery is repeatedly charged and discharged at a constant current under the conditions of
[0079] Example 7
[0080] An aqueous zinc ion battery electrolyte containing an amphiphilic zinc salt comprises a solute zinc salt and a solvent water, and is prepared by the following steps:
[0081] (1) Weigh 0.2 mol of N-(phenylsulfonyl)benzenesulfonamide and dissolve it in 300 mL of deionized water.
[0082] (2) Add 0.12 mol of zinc powder to the solution obtained in step (1), and react with magnetic stirring at 80° C. for 4 h.
[0083] (3) The mixture in step (2) is cooled to room temperature and filtered, the filtrate is collected, and then heated at 100° C. until all water is removed to obtain an amphiphilic organic zinc salt.
[0084] (4) The zinc salt prepared in step (3) is prepared into a solution with a concentration of 1 mol / L using deionized water, which is the final electrolyte used.
[0085] The electrolyte obtained in step (4) was used to assemble a 2032-type button-type zinc-zinc symmetrical battery with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). -2 , surface capacity is 1 mAh cm -2 The battery is repeatedly charged and discharged at a constant current under the conditions of
[0086] Example 8
[0087] An aqueous zinc ion battery electrolyte containing an amphiphilic zinc salt comprises a solute zinc salt and a solvent water, and is prepared by the following steps:
[0088] (1) Weigh 0.2 mol of N-(phenylsulfonyl)benzenesulfonamide and dissolve it in 300 mL of deionized water.
[0089] (2) Add 0.12 mol of zinc oxide to the solution obtained in step (1), and react with magnetic stirring at 80° C. for 4 h.
[0090] (3) The mixture in step (2) is cooled to room temperature and filtered, the filtrate is collected, and then heated at 110° C. until all water is removed to obtain an amphiphilic organic zinc salt.
[0091] (4) The zinc salt prepared in step (3) is prepared into a solution with a concentration of 1 mol / L using deionized water, which is the final electrolyte used.
[0092] The electrolyte obtained in step (4) was used to assemble a 2032-type button-type zinc-zinc symmetrical battery with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). -2 , surface capacity is 1 mAh cm -2 The battery is repeatedly charged and discharged at a constant current under the conditions of
[0093] Example 9
[0094] An aqueous zinc ion battery electrolyte containing an amphiphilic zinc salt comprises a solute zinc salt and a solvent water, and is prepared by the following steps:
[0095] (1) Weigh 0.2 mol of N-(trifluorosulfonyl)benzenesulfonamide and dissolve it in 300 mL of deionized water.
[0096] (2) Add 0.12 mol of zinc oxide to the solution obtained in step (1), and react with magnetic stirring at 80° C. for 4 h.
[0097] (3) The mixture in step (2) is cooled to room temperature and filtered, the filtrate is collected, and then heated at 100° C. until all water is removed to obtain an amphiphilic organic zinc salt.
[0098] (4) The zinc salt prepared in step (3) is prepared into a solution with a concentration of 1 mol / L using deionized water, which is the final electrolyte used.
[0099] The electrolyte obtained in step (4) was used to assemble a 2032-type button-type zinc-zinc symmetrical battery with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). -2 , surface capacity is 1 mAh cm -2 The battery is repeatedly charged and discharged at a constant current under the conditions of
[0100] Example 10
[0101] An aqueous zinc ion battery electrolyte containing an amphiphilic zinc salt comprises a solute zinc salt and a solvent water, and is prepared by the following steps:
[0102] (1) Weigh 0.2 mol of N-(trifluorosulfonyl)methanesulfonamide and dissolve it in 300 mL of deionized water.
[0103] (2) Add 0.12 mol of zinc oxide to the solution obtained in step (1), and react with magnetic stirring at 80° C. for 4 h.
[0104] (3) The mixture in step (2) is cooled to room temperature and filtered, the filtrate is collected, and then heated at 100° C. until all water is removed to obtain an amphiphilic organic zinc salt.
[0105] (4) The zinc salt prepared in step (3) is prepared into a solution with a concentration of 1 mol / L using deionized water, which is the final electrolyte used.
[0106] The electrolyte obtained in step (4) was used to assemble a 2032-type button-type zinc-zinc symmetrical battery with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). -2 , surface capacity is 1 mAh cm -2 The battery is repeatedly charged and discharged at a constant current under the conditions of
[0107] Comparative Example 1
[0108] An aqueous zinc ion battery electrolyte containing commercial zinc sulfate comprises solute zinc sulfate and solvent water, and is prepared by the following steps:
[0109] Commercial zinc sulfate heptahydrate was directly prepared into a solution with a concentration of 1 mol / L with deionized water, which was the electrolyte used in Comparative Example 1.
[0110] Using this electrolyte, a 2032-type button-type zinc-zinc symmetrical battery was assembled with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). -2 , surface capacity is 1 mAh cm -2 The battery is repeatedly charged and discharged at a constant current under the conditions of Figure 4 shown.
[0111] Comparative Example 2
[0112] An aqueous zinc ion battery electrolyte containing commercial zinc trifluoromethanesulfonate comprises a solute zinc trifluoromethanesulfonate and a solvent water, and is prepared by the following steps:
[0113] Commercial zinc trifluoromethanesulfonate was directly prepared into a solution with a concentration of 1 mol / L with deionized water, which was the electrolyte used in Comparative Example 2.
[0114] Using this electrolyte, a 2032-type button-type zinc-zinc symmetrical battery was assembled with a glass fiber separator (GF-A type) with a diameter of 19 mm and a zinc sheet with a diameter of 16 mm (thickness of 100 μm). -2 , surface capacity is 1 mAh cm -2 The battery is repeatedly charged and discharged at a constant current under the conditions of Figure 5 shown.
[0115] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An application of an amphiphilic organic zinc salt in an aqueous zinc ion battery electrolyte, the preparation steps of the amphiphilic organic zinc salt being: (1) dissolving an imide in water, adding a zinc source to the obtained solution and then heating it; (2) cooling the mixed solution obtained in step (1) to room temperature and filtering it, and heating the obtained filtrate to obtain an amphiphilic organic zinc salt; in, The imide is N-(phenylsulfonyl)benzenesulfonamide, and the amount is 0.2 mol; the zinc source is zinc oxide, and the amount is 0.12 mol; the imide, deionized water and the zinc source are reacted with magnetic stirring at 80° C. for 4 hours to obtain a mixed solution, and the filtrate obtained after the mixed solution is filtered is heated at 100° C. until all water is removed to obtain an amphiphilic organic zinc salt; the concentration of the amphiphilic organic zinc salt in the electrolyte is 1 mol / L.
Citation Information
Patent Citations
Sulfonylimide salt and method for producing the same
CN101980955A
Active material for secondary batteries, electrode for secondary batteries, secondary battery, battery pack, electric vehicle, electrical energy storage system, electric tool, and electronic device
CN104919630A
Lithium ion battery
CN112635822A
Aqueous zinc ion battery electrolyte and preparation method and application thereof
CN114976295A
Electrolytes containing mixed fluorocarbon / hydrocarbon imide and methide salts
CN1290408A